White by Another Name? Can Anti-Christian Bias Claims Serve as a Racial Dog Whistle? - Al-Kire, Rosemary L.; Miller, Chad A.; Pasek, Michael H.; Perry, Samuel L.; Wilkins, Clara L. (Psychological Science, 2024)
Four preregistered experiments ( N = 4,307) explored whether anti-Christian bias claims can discreetly signal White allyship among Christian American adults. In Experiments 1 and 2, reading about anti-Christian bias led White, but not Black, Christians to perceive more anti-White bias. Experiments 3 and 4 demonstrate the connection between Christian and White can be leveraged by politicians in the form of a racial dog whistle. In Experiment 3, White Christians perceived a politician concerned about anti-Christian bias as caring more about anti-White bias and more willing to fight for White people (relative to a control). This politician was also perceived as less offensive than a politician concerned about anti-White bias. In Experiment 4, Black Christians perceived a politician concerned about anti-Christian bias as less offensive than one concerned about anti-White bias yet still unlikely to fight for Black people. Results suggest “anti-Christian bias” can provide a relatively palatable way to signal allegiance to White people.